2007
DOI: 10.1002/pssb.200642286
|View full text |Cite
|
Sign up to set email alerts
|

Thermoluminescence and other optical studies on RbBr:Tb3+ crystals

Abstract: Optical absorption, photoluminescence, photostimulated luminescence (PSL) and thermoluminescence (TL) studies on RbBr : Tb 3+ crystals irradiated with X-rays is reported. The optical absorption in the UV region confirms the presence of terbium in the host matrix in the trivalent state. Photoluminescence of these crystals exhibits characteristic Tb 3+ emissions due to transitions from the 5 D 3 and 5 D 4 levels to various levels of the 7 F septet. On F-bleaching X-irradiated crystals Z 3 centers are observed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
(38 reference statements)
1
14
0
Order By: Relevance
“…In the recent past, our group carried out work on Ce 3+ , Tb 3+ and Sm 3+ doped potassium and rubidium halides respectively [21][22][23]. From this reported results, we observed the change in valence state of impurities on irradiation with X-rays (or) γ-rays.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…In the recent past, our group carried out work on Ce 3+ , Tb 3+ and Sm 3+ doped potassium and rubidium halides respectively [21][22][23]. From this reported results, we observed the change in valence state of impurities on irradiation with X-rays (or) γ-rays.…”
Section: Introductionmentioning
confidence: 73%
“…This absorption is due to Tb 3+ [23]. The reappearance of the absorption around 255 nm on F-light bleaching subsequent to irradiation indicates the Tb 3+ acts as a hole trap, ie.…”
Section: Optical Absorptionmentioning
confidence: 96%
See 2 more Smart Citations
“…A perturbed F center called a Z 3 center absorbs on the lower-wavelength side of the F band. Manimozhi et al [21] have also reported a similar kind of Z 3 centers in RbBr: Tb 3+ crystal. Considering this, it seems appropriate to assign the new absorption after F bleaching in the present work to Z 3 centers.…”
Section: +mentioning
confidence: 85%